PENGARUH TERPAAN PROMOSI ONLINE INSTAGRAM TERHADAP LOYALITAS KONSUMEN PADA “SAMBAL BU RUDY” - Shafa, Gantari; Sudaryanto, Edy (Sintesa, 2025)
In the midst of increasingly fierce business competition, companies must utilize online promotions to encourage first purchases and ensure customer satisfaction, which in turn can motivate repeat purchases and increase consumer loyalty. This study aims to determine the effect of exposure to online promotions on Instagram @pusol.burudy on consumer loyalty. The method used is a survey with a sample of 100 respondents, which measures the effect of online promotions through frequency, attention, and duration on consumer loyalty, which includes repeat purchases, product recommendations, and disinterest in competing products. In this study, stimulus-response (S-R) theory plays an important role, which states that stimuli such as online promotions can trigger certain responses such as consumer loyalty. The findings showed that the majority of respondents agreed that they were exposed to online promotions while viewing content on Instagram @pusol.burudy. In addition, respondents also showed high loyalty to Sambal Bu Rudy products. In conclusion, online promotion through Instagram @pusol.burudy has a significant effect on consumer loyalty, which supports the stimulus-response (S-R) theory.Keywords: Online Promotion Exposure1, Consumer Loyalty2, Instagram3